Spremljanje, modeliranje in analiza dogajanja med elektroporacijo celičnih membran in vivo ter njena uporaba - Pavšelj, Nataša (Medicinski razgledi, 2008)
Cell membrane is, in general, impermeable to larger molecules. However, the application of electric pulses to cells, either in suspension or as tissue, causes the electroporation of the cell membrane, increasing its permeability and making it possible for larger molecules which otherwise cannot cross the membrane, such as drug molecules or the DNA, to enter cells. The most widely used electroporation-based biomedical applications are electrochemotherapy, gene electrotransfer and transdermal drug delivery. A high level of cell membrane electroporation is the objective of all applications. However, caution should be exercised in order not to damage the tissue with excessivelystrong electric fields. The outcome of electroporation-based treatments can be assessed by various methods a certain time after treatment. The course of tissue permeabilization can be evaluated by measuring tissue conductivity changes during pulse delivery. Furthermore, cell and tissue electroporation can be described by means of analytical methods or numerical modeling which offers useful insight into the understanding of the underlying biological processes and can help us plan future experiments and develop new electrodes and protocols.
Keywords: Celična membrana, propustnost; Cell Membrane; Cell Membrane Permeability; Gensko zdravljenje; Electroporation; Celična membrana; Drug Delivery Systems; Zdravilo, sproščanje, sistemi; Gene Therapy; Elektroporacija; tumor; Neoplasms; Novotvorbe; Therapy; fiziologija